(untitled) (Texas Journal of Medical Science, 2023)
The ongoing worldwide intensive chemicalization of agriculture leads to the fact that annually a large number of various foreign chemicals (xenobiotics), including pesticides, enter the planet’s biosphere, that is, the environment for the habitat of all living things, including humans. As a result of careless handling of pesticides, as well as accidental or intentional ingestion of the drug, acute and subacute poisoning occurn